Biography – біографіка – біографістика – біобібліографія: понятійний арсенал історико-біографічних досліджень - Попик, В.І. (Український історичний журнал, 2015)
Розглядається комплекс ключових теоретичних понять історико-біографічних
досліджень, серед яких «біографія», «біографіка», «біографістика, «біобібліографія
», «ресурси біографічної інформації» та інші, а також питання їх змістового
наповнення, співвідношення, коректного вживання термінів. Звернуто увагу
на відмінності у використанні зазначеної термінології у соціогуманітаристиці
різних країн. Обґрунтовано позиціонування «біографістики» як спеціальної
історичної дисципліни, що вивчає досвід та теоретичні проблеми біографічних
досліджень, розробляє методичні засади підготовки різних видів історико-
біографічних видань, формування ресурсів біографічної інформації. Наголошено
на необхідності розмежування «біографістики» й «біографіки», під якою слід розуміти
напрям наукової та літературної біографічної творчості, що об’єднує різні види біографічних досліджень і публікацій. Complex of key theoretical concepts of historical and biographical studies: “biography”,
“biographica”, “biographistica”, “biobibliography”, “resources of biographical
information”, questions of their semantic content, correlation and correctness for
terms using were under investigation in the article. Attention is paid to the differences
in the use of mentioned terminology in social and humanitarian sciences in different
countries. Substantiated positioning of “biographistica” as a special historical
discipline that studies the experience and theoretical problems of biographical
research, develops methodological foundations of preparing of various kinds of historical
and biographical publications, and forms the resources of the biographical
information. Highlighted the necessity of separation of the notions “biographistica”
and “biographica”, the latter shall be understood as the direction of the scientific and
literary biographical work, which brings together different types of biographical studies and publications.